Effect of Different Strain of Kappaphycus alvarezii on Specific Growth Rate - Dodi Hermawan (JURNAL PERIKANAN DAN KELAUTAN, 2015)
This study aimed to analyze the differences strains in the characteristics of the specific growth rate Kappaphycus alvarezii. This research was conducted in the waters of Lontar village, Serang Banten for 45 days in May-June. The treatment used is a strain difference seaweed seedlings derived from tissue culture (KJL-Lampung), strain “Jumbo kuning coklat” (JKC-Lontar) and strain “Jumbo hijau botol” (JHB Taman Jaya). This study used an experimental method using a completely randomized design (CRD) with three treatments and each 3 replication. Culture method of seaweed used off-bottom methode. Parameters measured were the specific growth rate and water quality. The results showed that the specific growth rate in seaweed Kappaphycus alvarezii strain JHB-Taman Jaya higher than the specific growth rate of seaweed Kappaphycus alvarezii strain JKC-Lontar and KJL-Lampung. Therefore, for maintenance in May-June should be planted seaweed Kappaphycus alvarezii strain JHB-Taman Jaya.